Iliosacral screw corridors in Japanese subjects: a study using reconstruction CT scans - Iga, Toru (OTA international : the open access journal of orthopaedic trauma, 2021)
To investigate the characteristics of iliosacral (IS) screw corridors of Japanese pelves. Computer tomography images of 42 adult Japanese subjects without any pelvic injury were analyzed at a workstation. Using the manual reconstruction function, the width of a simulated horizontal corridor for an IS screw on the true coronal and true axial planes in the upper (S1), second (S2), and the third (S3) sacral segments was measured. For pelves without an adequate S1 corridor, a cranially tilted corridor was sought. A corridor was defined as "adequate" if its width on both planes was 10 mm or more. An adequate horizontal corridor was found in S1 in 17 (40.5%) subjects, in S2 in 29 (69.0%) subjects, and in S3 in no subject. An independent factor affecting the adequacy of the S1 corridor was the adequacy of the S2 corridor (OR: 0.09). Similarly, an independent factor affecting S2 adequacy was S1 adequacy (OR: 0.10). A tilted, 10 mm diameter corridor was found in all 25 subjects who did not have an adequate horizontal corridor in the S1 segment. The angle required to obtain a 10 mm diameter corridor inversely correlated with the diameter of a horizontal corridor on the true coronal plane (R = -0.713, = .000). The characteristics of IS screw corridors in the 42 Japanese subjects were similar to those reported in previous studies conducted in the West. The importance of preoperative planning using reliable techniques, such as three-dimensional reconstruction, should be emphasized.Level of evidence: Diagnostic Level III. See Instructions for Authors for a complete description of level of evidence.